Evaluation and Investigation of the Prevalence of Superficial Mycosis among Primary Schools Pupils in Al-Dewaniyah Governorate, Iraq - Sara K. Al-Zubaidi (Journal of Global Pharma Technology, 2016)
Background: The Superficial mycosis infections are the widespread types of mycosis among children primary schools. Objective: To detection and evaluation the extent and prevalence of superficial mycosis infection among primary school pupils in Al-Dewaniyah province. Subjects and methods: The survey included the selection of the pupils were randomly selected based on those with tinea (ringworm) lesions sample of 103 pupils (males 81, females 22) respectively from ten primary schools (six male and four female schools), they clinically diagnosis dermatophytoses, in the Diwaniyah Teaching Hospital, Dermatology unit, during a period from the beginning of December 2018 till the final February 2019. The specimens were collected in sterile plastic Petri dishes or sterile plastic envelopes and consisted of skin scales, hairs, or clippings from fingernails and toenails. The samples of fingernails and toenails were cut or to get mycelial elements. Results: The results of identity and incidence of the dermatophytes and non-dermatophytes isolated were revealed that dermatophytic isolation " Tinea" was 36/103(34%) among patients and this percentage was distributed to various clinical cases of ringworm ''tinea'', Mean age of patients enrolled in the present study was 20.11+10.99 years with a range of 7 to 13 years, According to gender patients were classified into 25 male s (69%) and 11 females (31 %). dermatophytes infections Is a problem in the health system of many developing countries and influences all ages chiefly primary pupils.  Conclusion: The current study prevalence of superficial mycosis among pupils of primary school was significant risk factors assessed such as poor personal hygiene, overcrowding. Consequently, proper health education, personal and environmental sanitation, provision of infrastructure, primary health care and regular clinical studies are recommended for these primary school pupils.Keywords: Dermatophytes, Primary school pupils, Mycelia, Superficial mycosis.